300 μJ, 3 W, few-cycle, 3 μm OPCPA based on periodically poled stoichiometric lithium tantalate crystals - Zou, Xiao (2021)
We report a carrier–envelope-phase-stable 3 μm optical parametric chirped-pulse amplifier (OPCPA), based on periodically poled stoichiometric lithium tantalate nonlinear crystals, which delivers 306 μJ pulse energy at 10 kHz repetition rate and 61 fs pulse width. A 2 mm thick YAG crystal is employed to further compress the pulses to 21 fs corresponding to two-cycle pulse duration, with no ionization loss observed. Driven by the OPCPA, high-order harmonics up to the 15th order are generated in ZnO crystal, and one-order enhancement of the harmonics intensity is demonstrated with nonlinear compression.